Pengalaman Perokok dalam Terapi Berhenti Merokok dengan Metode Spiritual Emotional Freedom Technique (SEFT) di Desa Cipanjalu Kabupaten Bandung Tahun 2019 - Ruhyat, Ejeb (Sehat MasadaJurnal, 2020)
Cigarettes and smoking are problems that are still difficult to resolve to date. About 4.9 million people in developing countries died of smoking in 2003. This study aimed to determine the experience of smokers in smoking cessation therapy with the Spiritual Emotional Freedom Technique (SEFT) method in Cipanjalu Village, Bandung Regency in 2019. The type of research conducted was The type of research used is qualitative research with a phenomenological approach. Informants in this study were smokers who had been treated as many as 4 people. The results showed Based on the response or reaction when smoking cessation therapy was found that the reaction was almost the same, based on the desire to smoke after smoking cessation therapy that found all experienced a decrease in desire to smoke again, based on the length of time they did not smoke after different therapies - difference, Based on the number of cigarettes smoked after stopping smoking therapy, it was found that the number of cigarettes smoked every day varied after treatment, but all said they experienced a decrease in the number of cigarettes smoked. It is recommended to create a smoke-free environment with a shared commitment in the RW to create a non-smoking environment.